Green school audit of twenty two schools in Pune city - Vaidya, Varsha; Gothankar, Jayashree; Pore, Prasad; Patil, Reshma; Murarkar, Sujata (International Journal Of Community Medicine And Public Health, 2018)
Background: The Green school audit is a tool designed to help school communities to audit their use of natural resources. It provides schools with the methodology to become environmental managers by assessing themselves. Green school audit was part of green games initiatives of commonwealth youth games Pune 2008 with objective to carry out environmental audit of schools involving school children. Methods: The programme was carried out from March 2008 to October 2008 as a part of Green Games initiative of Commonwealth Youth Games. Twenty two schools voluntarily participated in this programme. Four medical students per school and one teacher from the Department of Community Medicine were posted per school to train one school teacher and twenty five school children about the audit. Each school was provided with a Green School manual; a do it yourself (DIY) guide that helped students to assess the five key elements that comprises their school’s environment namely air, water, land, energy and waste. Results: 15 schools were in green zone for air audit, 9 schools were in green zone for water audit, 11 schools were in green zone for land audit, 13 schools were in green zone for waste audit and 10 schools were in green zone for energy audit. Conclusions: This assessment helped each participating school to identify where it currently stood and where it should be with regard to the environmental standards prescribed in the manual. This is a learning programme for students helping them to develop environmentally conscious attitudes and ultimately a responsible behavior.